The Relationship between Air Transport and Economic Growth in Turkey: Cross-Regional Panel Data Analysis Approach - Baltaci, Nuri; Sekmen, Ozlem; ., Gizem Akbulut (Journal of Economics and Behavioral Studies, 2015)
Today, the economic and social effects of the airports on the region they are located are widely accepted throughout the world including Turkey. In developing countries transportation sector is a significant tool of development. Since millennium there has been a great growth in the number of people who prefer air transportation in Turkey. The decrease in the cost of the transportation of both passengers and freight in air transport leads the increase of its accessibility. In this concept when a region has an active airport it helps to increase the region’s competitiveness and support its economic, social and cultural development. The aim of this study is to analyze whether an active airport and its traffic frequency have an effect on country’s macroeconomic indicators. In this study region - fixed effect and two stage least square (2SLS) models are applied with using panel data for 26 sub-regions at NUTS 2 level in Turkey period of 2004 - 2011. The results of this study support that increasing in number of active airports and its traffic frequency have a positive effect on regional economic growth.